Reducing unemployment : the Humphrey-Hawkins and Kemp-McClure bills. - American Enterprise Institute for Public Policy Research (Washington : American Enterprise Institute for Public Policy Research, 1976)
This book contains Humphrey-Huwkins and Kemp-McClure legislative bills design to reduce the rate of unemployment in the united state under the American enterprise institute for public policy research.
Includes bibliographical references.
asm; 26/02/19
Loans
Keywords: Full employment policies; Unemplyment; United States